Effect of velvet worms (Onychophora) on culture and art during the period 2014-2019 ; representations, subjects and worldwide distribution (UNED Research Journal, 2020)
Introduction: Velvet worms are a terrestrial invertebrate group, considered "living fossils" by some, with over 520 million years of existence. They capture prey with a sticky secretion, and some species have a placenta. By being animals with such peculiar features, but not traditionally selected as “charismatic species”, it is interesting to see the cultural and artistic influence that they currently may have. Objective:  This research reports how the phylum Onychophora has influenced culture and art in the years after the study by Monge-Nájera & Morera-Brenes five years ago. Methods: I searched the cultural and artistic works related to Onychophora on the web, through the most common names these animals receive in different countries, to assess if the number of products have increased. Furthermore, I classified the works in subjects and according to positive or negative depictions. Results:  I found 336 cultural and artistic works related to Onychophora, most of them cartoons, then sublimated products, craftworks, edited images and videos. I also found 6 outstanding subjects, and in most of the cases, the works carry a positive image. The countries with the most total works are the United States, Australia and New Zealand, while per capita (per million inhabitants) are New Zealand, Costa Rica and Australia. Conclusions: The onychophore’s external morphology mainly, along with their hunting mechanism, have generated an unexpected interest in culture and arts.
Keywords: Velvet worms, oral papillae, anthropomorphism, charismatic species, invertebrates in culture.; velvet worms; oral papillae; anthromorphism; charismatic species; invertebrates in culture